2002
DOI: 10.1111/j.1471-0528.2002.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual compared with oral misoprostol in term labour induction: a randomised controlled trial

Abstract: Fifty micrograms of sublingual misoprostol every four hours has the same efficacy and safety profile as compared with 100 microg orally, but the oral route might be preferred by women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 13 publications
1
14
3
Order By: Relevance
“…Overall, rates of uterine hyperstimulation syndrome were not higher in this study (7.1%) than in other clinical trials of 50 μg of sublingual misoprostol for labour induction (5–8%) 15,16 . The incidence of hyperstimulation syndrome in two recent studies of sublingual misoprostol 50 μg was only 1.6–2% 11,12 . Despite the lower hyperstimulation syndrome rate, the incidence of caesarean section for fetal distress and instrumental vaginal delivery in both the above mentioned studies was higher than in the present study (6.0 and 22%; 11 and 27% versus 10 and 7.1%, respectively) 11,12 .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Overall, rates of uterine hyperstimulation syndrome were not higher in this study (7.1%) than in other clinical trials of 50 μg of sublingual misoprostol for labour induction (5–8%) 15,16 . The incidence of hyperstimulation syndrome in two recent studies of sublingual misoprostol 50 μg was only 1.6–2% 11,12 . Despite the lower hyperstimulation syndrome rate, the incidence of caesarean section for fetal distress and instrumental vaginal delivery in both the above mentioned studies was higher than in the present study (6.0 and 22%; 11 and 27% versus 10 and 7.1%, respectively) 11,12 .…”
Section: Discussioncontrasting
confidence: 84%
“…The objective of this study was to compare the efficacy and safety of 50 μg of sublingual misoprostol with vaginal misoprostol in its currently recommended dose of 25 μg administered at 4‐hour intervals for labour induction at term. We decided to use the 50‐μg sublingual misoprostol dose because this dosage seems to be effective and safe in previous studies when compared with oral misoprostol 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Three studies were identified that compared sublingual or buccal with otherwise administered misoprostol [19–21]. One study ( n = 157) compared buccal (200 μg) with vaginal (50 μg) misoprostol administered six hourly [19].…”
Section: Resultsmentioning
confidence: 99%
“…None of these differences were statistically significant, nor were any other outcome variables. Two studies ( n = 350) compared 50 μg of sublingual with 50 and 100 μg of oral misoprostol administered every 4 h [20,21]. When the same dosage was used by both routes, the sublingual misoprostol appeared associated with less failure to achieve vaginal delivery after 24 h (24% versus 38%; OR 0.52, 95% CI 0.22–1.22), less oxytocin augmentation (34% versus 46%; OR 0.60, 95% CI 0.27–1.36) and less cesarean section (16% versus 30%; OR 0.44, 95% CI 0.17–1.17), but none of these differences were statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…8 11 However, there are multiple studies supporting efficacy and safety of sublingually administered misoprostol when compared with the vaginal and oral routes for IOL. 12 13 14 15 16 …”
Section: Discussionmentioning
confidence: 99%